2013
DOI: 10.1016/j.scitotenv.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene inhibits the role of the bioturbator Tubifex tubifex in river sediment biogeochemistry

Abstract: The interactions between invertebrates and micro-organisms living in streambed sediments often play key roles in the regulation of nutrient and organic matter fluxes in aquatic ecosystems. However, benthic sediments also constitute a privileged compartment for the accumulation of persistent organic pollutants such as PAHs or PCBs that may affect the diversity, abundance and activity of benthic organisms. The objective of this study was to quantify the impact of sediment contamination with the PAH benzo(a)pyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 88 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…As with other contaminants, biotic interactions with sediments can influence the form and distribution of PAHs in rivers. Mermillod-Blondin et al (2013), for example, document how lower concentrations of the PAH benzo(a)pyrene do not limit the survival of a tubifex worm that bioturbates river sediment, but the PAH does inhibit worm activity and the associated microbial processes that reduce contaminant concentrations.…”
Section: Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…As with other contaminants, biotic interactions with sediments can influence the form and distribution of PAHs in rivers. Mermillod-Blondin et al (2013), for example, document how lower concentrations of the PAH benzo(a)pyrene do not limit the survival of a tubifex worm that bioturbates river sediment, but the PAH does inhibit worm activity and the associated microbial processes that reduce contaminant concentrations.…”
Section: Activitymentioning
confidence: 99%
“…Biotic activities can also alter the distribution of contaminants via processes such as bioturbation or the chemical form of the contaminant via processes such as microbial reactions (Mermillod-Blondin et al, 2013).…”
Section: Broader Implications Of Contaminated Sedimentsmentioning
confidence: 99%
“…Oxygen inhibits enzymes involved on denitrification but also stimulates sedimentary nitrification that usually provides the major source of nitrate for denitrification (Herbert, ). Bioturbation can promote microbial activities (Kogure and Wada, ; Satoh et al ., ; Mermillod‐Blondin et al ., ) and modify microbial communities structures (Laverock et al ., ) associated with different aerobic processes and anaerobic organic matter degradation (Berthe‐Corti and Höpner, ; Grossi et al ., ; Papaspyrou et al ., ) as also demonstrated by 16S rRNA gene‐based studies in hydrocarbon‐, oil‐ or pesticide‐contaminated sediments (Cuny et al ., ; Monard et al ., ). To the best of our knowledge, only one study revealed the concomitant effect of oil and bioturbation (Gilbert et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many marine species rework sediment and thus play a key role in benthic ecosystems by shaping local geochemical gradients and resource distribution (e.g., Aller, 1982;Solan et al, 2004;Meysman et al, 2006). By contrast, in freshwaters, the bioturbation ability of only a few species or taxonomic groups, including tubificids, chironomids, and clams, has been investigated (Fisher et al, 1980;Matisoff & Xiaosong, 1998;Ciutat et al, 2005;Stief & de Beer, 2006;Lagauzère et al, 2009;Mermillod-Blondin et al, 2013;Majdi et al, 2014a). Yet, the recent work of De Nadaï- Monoury et al (2013Monoury et al ( , 2014 has provided a wider overview of bioturbator diversity in freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%